THE EFFECTIVENESS OF INTERACTIVE LANGUAGE TEACHING IN IMPROVING STUDENT’S SPEAKING SKILL - Ferlya Elyza; Ayu Rahmi (Center for Research and Community Service (LPPM) University of Abulyatama, 2017)
Interaction is one of the important activities in language teaching learning process. The teacher needs approach and technique that can make the students creative, interactive and more enthusiastic in speaking classroom. One of the interactive techniques is a small group work. Therefore, the researcher adapted small group work technique. The purposes of the study are to find out the problems faced by the students in speaking and to find out that teaching speaking by using small group will be effective in solving the problems faced by students. The method which was used in this study was quantitative experimental research. The population of this study at the first grade students of SMAN 1 Krueng Barona Jaya. The researcher used random sample. The researcher took two classes, those are X-IA3 and X-IA2. The number of sample of this research are 14 students for each class. Class X-IA3 was experimental class and class X-IA2 was as control class. The data was analyzed by using statistical formula. The problems that are generally faced by students in speaking skill are their inability in expressing their idea and afraid of making mistake. The result shows that interactive language teaching by using small group work is very effective in improving student’s speaking skill . It is based on the result of t-score which is higher than t-table. The value of the t-table list found =2.15 and t-score = 3.04. It means the hypothesis can be accepted. It indicates that the first grade students of SMA 1 Krueng Barona Jaya who are taught speaking by using small group work get higher score than the students who are taught without using small group work. Based on the result of the study, the researcher suggests to use small group technique in teaching speaking because it can increase the students' achievement in speaking skill.